Bu-Shen-Ning-Xin decoction alleviates premature ovarian insufficiency (POI) by regulating autophagy of granule cells through activating PI3K/AKT/mTOR pathway. (2nd September 2022) - Dou, Xiaoqing; Jin, Xin; Chen, Xingbei; Zhou, Qun; Chen, Hanyu; Wen, Mingxiao; Chen, Wenjun
Abstract: Purpose: To explore the therapeutic effects of Bu-Shen-Ning-Xin decoction (BSNXD) on POI and the underlying mechanism. Methods: VCD was used to induce the in vivo and in vitro POI model. HE staining was used to evaluate the pathological state of ovarian tissues. ELISA was used to detect the production of hormones in the serum and granule cells (GCs). An immunohistochemical assay was used to determine the expression of ATG7 and p-AKT in the ovarian tissues. The number of oocytes in POI rats was counted. The mitochondrial membrane potential (MMP) in oocytes and GCs was detected by flow cytometry. A Western blot assay was used to measure the expression of AKT, p-AKT, p-mTOR, mTOR, S6K, p-S6K, ULK1, p-ULK1, Beclin-1, Bcl-2, LC3-II, LC3-I, ATG7, and cleaved Caspase3. The numbers of autophagosomes were detected by transmission electron microscope and autophagic flux assay. The CCK-8 assay was used to detect the cell viability. Results: Decreased primary follicles in the ovarian tissues, elevated concentration of FSH, and LH, suppressed concentration of E2 and AMH in the serum, reduced number of oocytes, and mitochondrial dysfunction in oocytes induced by VCD were significantly reversed by BSNXD. Activated autophagy state and inhibited PI3K/AKT/mTOR pathway stimulated by VCD in both ovarian tissues and GCs were dramatically reversed by BSNXD. The protective effect of BSNXD on VCD-treated GCs was abolished by LY294002, an inhibitor of the PI3K/AKT/mTOR pathway. Conclusion: Our data revealed that BSNXD alleviated POI by regulating autophagy of granule cells through activating PI3K/AKT/mTOR pathway.